Prevalence of spondyloarthritis and its subtypes in southern Sweden. Issue 6 (2nd February 2011) - Haglund, E; Bremander, A B; Petersson, I F; Strömbeck, B; Bergman, S; Jacobsson, L T H; Turkiewicz, A; Geborek, P; Englund, M
Abstract : Objective: To estimate the prevalence of spondyloarthritis and its subtypes. Methods: The Swedish healthcare organisation comprises a system where all inpatient and outpatient care is registered by a personal identifier. For the calendar years 2003–7, all residents aged ≥15 years in the southernmost county of Sweden (1.2 million inhabitants) diagnosed by a physician with spondyloarthritis (ankylosing spondylitis (AS), psoriatic arthritis (PsA), inflammatory arthritis associated with inflammatory bowel disease (Aa-IBD) or undifferentiated spondylarthritis (USpA)) were identified. To obtain valid point estimates of prevalence by the end of 2007, identification numbers were cross-referenced with the population register to exclude patients who had died or relocated. Results: The authors estimated the prevalence of spondyloarthritis (not including chronic reactive arthritis) as 0.45% (95% CI 0.44% to 0.47%). The mean (SD) age of patients with prevalent spondyloarthritis by the end of 2007 was 53 (15) years. Among the component subtypes, PsA accounted for 54% of cases, AS 21.4%, USpA 17.8% and Aa-IBD 2.3% with a prevalence of 0.25%, 0.12%, 0.10% and 0.015%, respectively. The remaining 6.4% had some form of combination of spondyloarthritis diagnoses. The prevalence of spondyloarthritis at large was about the same in men and women. However, the subtype PsA was more prevalent in women and AS was more prevalent in men. Conclusion: In Sweden the prevalence of spondyloarthritis leading to a doctor consultation is not much lower than rheumatoid arthritis. PsA was the most frequent subtype followed by AS and USpA, and the two most frequent subtypes PsA and AS also display some distinct sex patterns.